A review on the impact of distributed energy resources uncertainty on distribution networks - Annathurai, Vinodh; Gan, Chin Kim; Ibrahim, Khairul Anwar; Baharin, Kyairul Azmi; Ab Ghani, Mohd Ruddin (Praise Worthy Prize, 2016)
Recently, emerging technologies such as Photovoltaic system (PVs), Electric Vehicle (EV), micro Combined Heat Pump (µCHP) and Electric Heat Pump (EHP) have become preferable choices as means to address the climate change challenge. However, these emerging technologies often suffer from intermittency issues such as solar radiation variation and EV charging. The increasing penetration of such technologies in the distribution network has the potential to cause network problems. Hence, the analysis of the impact of these emerging technologies on distribution network is crucial, particularly by considering its intermittent nature. Therefore, this paper presents a review on the uncertainty nature of emerging technologies, followed by the Monte Carlo simulation approach that can be used to analyze the problems.The analysis focuses on the effects of different time resolution on two aspects--voltage problem and utilization level index. Results indicate that the time resolution strongly correlates with the voltage problem. High fluctuations visible at short time intervals are subjected to smoothing as the time interval increases. However, the utilization index level is relatively unaffected at different time resolutions